Biological reference points for north-east Arctic cod and haddock - Jakobsen, Tore (ICES, 1989)
It has been suggested by ACFM that Fmed might be preferable to Fmax as a biological reference point for the North-East Arctic cod. However, the Fmed level of more than twice Fmax appeared high, and it was known to have been based on biased historie SSB estimates. Also, the robustness of Fmed and its related points Flow and Fhigh to changes in the parameters used for their estimation has not been thoroughly investigated. The effect of the various parameters on the biological reference points for North-East Arctic cod and haddock is tested.